2018
DOI: 10.17113/ftb.56.03.18.5658
|View full text |Cite
|
Sign up to set email alerts
|

Microbial keratinases: enzymes with promising biotechnological 4 applications

Abstract: SUMMARYKeratin is a complex and structurally stable protein found in human and animal hard tissues, such as feathers, wool, hair, hoof and nails. Some of these, like feathers and wool, represent one of the main sources of protein-rich waste with significant potential to be transformed into value-added products such as feed, fertilizers or bioenergy. A major limitation impeding valorization of keratinous substrates is their recalcitrant structure and resistance to hydrolysis by common proteases. However, specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 147 publications
(206 reference statements)
2
83
0
Order By: Relevance
“…Concerning to the production of keratinolytic protease by B. cytotoxicus species, it was observed that keratinases expression was inducible and occurred only in the presence of feathers as an exogenous inducer when it was incubated at 50 • C. Similar inducibility has been found in varieties of microorganisms [27,52,53].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Concerning to the production of keratinolytic protease by B. cytotoxicus species, it was observed that keratinases expression was inducible and occurred only in the presence of feathers as an exogenous inducer when it was incubated at 50 • C. Similar inducibility has been found in varieties of microorganisms [27,52,53].…”
Section: Discussionsupporting
confidence: 56%
“…However, only few thermophilic bacteria are known to produce keratinases. Thus, there is still a need to find more robust and specific thermostable keratinolytic enzymes, which could be applied to fulfill the increasing demand of detergent, leather, textile, food, and pharmaceutical industries [12,[22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Keratinase, on the other hand, displays unique attributes that may be exploited in bioprocessing such as keratin bioconversion to useful products, textile treatment, leather depilation, and other industrial applications (Fang et al, 2013;Kalaikumari et al, 2019). Direct evolution (DE), site-directed mutagenesis (SDM), site-saturation mutagenesis (SSM), truncation, and fusion are among the protein engineering techniques that have been adopted to create robust enzymes (Gong et al, 2015;Yang et al, 2017;Vidmar and Vodovnik, 2018), and it has been successfully applied to overcome the limitations faced with biocatalysts (Fang et al, 2019). Site-directed mutagenesis depends on the protein structure alterations, meanwhile directed evolution functions based on a randomly generated library of mutants for the comprehensive discovery of promising variants (Gupta et al, 2013;Fang et al, 2017b).…”
Section: Keratinase Catalytic Efficiency Enhancement -A Protein Enginmentioning
confidence: 99%
“…Such enzymatic deconstruction processes are useful during treatment or valorization of polymeric by‐products, treatment of materials for biotechnological applications, and preparation of high‐value hydrolysates from complex polymers. Examples of enzymes that have been used in this category are keratinases for the degradation of recalcitrant keratinous proteins in hair, horns, wool, feathers, hooves, and nails (Vidmar & Vodovnik, 2018). These keratinous materials typically contain over 85% crude proteins (Luan et al., 2019).…”
Section: Prospective Applications Of Extremozymes In the Food Industrymentioning
confidence: 99%